Strategi Meningkatkan Cuan dalam Islam - Mutawali,; Ludvy, Achmad; Hasanah, Yenny Merinatul (Praxis: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this activity is formulate a sharia-style personal financial management strategy during a pandemic. The purpose of this activity is because the GP Anshor community finds it difficult to manage finances that have low income, plus there are lots of unlimited needs and desires, they cannot distinguish between needs and wants. what they think is pleasure and satisfaction to get what they want. so that often his income is not sufficient for the needs of his family. This service uses an educational and training approach to the Anshor youth community in the Pagedangan sub-district, Tangerang Regency who does not yet know how to manage personal finances according to Islamic law. Furthermore, this study uses the actions taken by the Anshor youth community participants who participated in this training to discuss the problem of sharia financial management that does not conflict with sharia arguments and the blessings of the hereafter. The existence of sharia financial management is a new science for them to get pleasure and also blessings in both the world and the hereafter. From the results of this training, the Anshor youth community can practice the results of this training from the form of financial management which is not only aimed at world affairs, but there are hereafter affairs that must be managed financially, and can optimize alms, zakat, waqf as investment instruments that can multiply their income from all sides in accordance with the advice that is commanded in Islam. This activity is of course aimed at getting the blessings of using this management perfectly and avoiding actions against their lust for the desires that exist in them and prioritizing their main needs.